Analysis of Employee Behavior, Environmentally Friendly Intellectuals, and the Advantages of Green Motivation Towards Green Innovation in the DKI Jakarta Provincial Tourism Office - Wenny Desty Febrian; Ibnu Haris Nasution (International Journal of Advanced Technology and Social Sciences, 2023)
At this time, tourism is the most interesting thing for local and international tourists to visit. The world of tourism was not running due to the impact of Covid 19 in the previous 2 years, but now tourism has become the main attraction after the Covid 19 period has passed. Of course, each region has different attractions in terms of tourism. DKI Jakarta Province has interesting attractions to visit, there are many small islands that are beautiful to the eye, and attractive as a place to relieve fatigue. Therefore, it needs to be supported by environmentally friendly employee behavior, environmentally friendly intellectuals, and superior green motivation, which aims to increase green innovation in this place. The aim of this research is to examine the influence between environmentally friendly employee behavior and green innovation, examine the influence between green intellectuals and green innovation, and examine the influence between green competitive advantage and green innovation. On this occasion, the researcher wants to see the extent of the influence of the employee behavior variable (X1 ), friendly intellectuals (X2), and the superiority of green motivation (X3) towards green innovation (Y) in DKI Jakarta Province. This research method is a literature review that compares several existing theories with previous research. The output of this research was submitted to an international journal, namely Copernicus